Study on particle fluidization characteristics and separation effect of coarse slime fluidized flotation - Qinglin YIN; Shihao DING; Yiqing ZHANG; Qi HE; Yaowen XING; Xiahui GUI (Meitan kexue jishu)
The new gas-liquid-solid fluidized bed flotation technology can realize the efficiency recovery of coarse particles based on the principle of refloating coupling. Taking 1.0-0.5 mm coarse coal slime as the research object, the effects of water velocity, inflating gas flow, concentration of collector and frother on the fluidization characteristics and separation effect of two-dimensional fluidized-bed in the laboratory were systematically investigated. The results show that the fluctuation of pressure signal can be effectively reduced and the stability of fluidized-bed can be improved by increasing the water velocity, reducing the inflating gas flow and adding frother and collector. Reducing the inflating gas flow can reduce the apparent gas velocity of the fluidized-bed, while increasing the water velocity and adding the frother will reduce the bubble size through the shear effect of the upflowing fluid and the reduction of the surface tension, and the adding of the collector will make the adhesion of the bubble to the particles and reduce the floating speed of the bubble. With the increase of water velocity and inflating gas flow, the ash content of concentrate first decreases and then increases, but the tailling ash content has a slightly different trend. Too high inflating gas flow will disturb the fluidized-bed and lead to serious mixing，then the tailling ash content will increase. The appropriate addition of collector and frother will further reduce the ash content of concentrate, which is due to the adhesion of flotation bubbles on the surface of coarse particles, reducing its apparent density and strengthening the density separation effect. However, excessive addition of agents may lead to the occurrence of flotation entrainment and increase the ash content of concentrate. Finally, a semi-industrial test of fluidized bed flotation with a diameter of 200 mm was carried out, and the best separation index was obtained with 1.0-0.25 mm coarse slime as feed at water velocity of 15 L/min, inflating gas flow of 1.5 L /min, collector of 200 g/t and frother of 400 g/t. Ash content and yield of concentrate were 9.34% and 90.13%, and tailling ash content and yield were 38.51% and 9.87%, respectively. This study is of great significance for the realization of fluidized-bed stability control and efficient recovery of coarse slime in fluidized bed flotation process.